Resilience of Sultana (Vitis Vinifera) to Drought and Subsequent Recovery: Field Evaluation of Nine Rootstock Scion Combinations - Sommer, K.J .; Hancock, F.; Downey, M.O. (South African Journal of Enology and Viticulture, 2016)
The work reported here surveyed the recovery of H4 Sultana from severe drought when grafted to 9 rootstocks (101- 14 Millardet, 116-60 Lider, 187-24 Lider, 5BB Kober, 1103 Paulsen, Ramsey, 140 Ruggeri, Schwarzmann and selfgrafted Sultana). Vines did not receive any irrigation water from July until late February in the 2007 to 2008 season but were watered normally thereafter to facilitate their recovery. Large differences in leaf retention and fruit yield were apparent among rootstocks just before rewatering and were quantified in order to document the influence of rootstock on vine resilience and the potential for subsequent recovery. Vines grafted to the rootstocks 101-14 Millardet, Schwarzmann and self-grafted Sultana performed poorly during drought and some vines did not recover after re-watering. Vines on other rootstocks retained a viable leaf canopy and showed good potential for recovery. Vines grafted to 187-24 Lider performed best showing high resilience during and good recovery from drought.